Faktor-Faktor yang mempengaruhi Earnings Persistence - Sri Wahyuni; Nurainun Bangun (Media Ilmiah Akuntansi, 2023)
The purpose of this study was to determine the effect of accruals, sales volatility, and managerial ownership on earnings persistence in companies sector of basic industrial and chemicals, miscellaneous industries and consumer goods listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. This study used a sample of 31 companies, that selected using purposive sampling and Eviews 12.0 application to process the data. The results showed that the independent variables simultaneously (F Test) affect earnings persistence. The results of the T test indicate that the sales volatility variable has a significant effect on earnings persistence. Meanwhile, accruals and managerial ownership variables have no significant effect on earning persistence